2015
DOI: 10.1103/physrevlett.114.067601
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity and Heterogeneity in Plastic Crystals Studied by Nonlinear Dielectric Spectroscopy

Abstract: The glassy dynamics of plastic-crystalline cyclo-octanol and ortho-carborane, where only the molecular reorientational degrees of freedom freeze without long-range order, is investigated by nonlinear dielectric spectroscopy. Marked differences to canonical glass formers show up: While molecular cooperativity governs the glassy freezing, it leads to a much weaker slowing down of molecular dynamics than in supercooled liquids. Moreover, the observed nonlinear effects cannot be explained with the same heterogenei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 52 publications
3
57
0
Order By: Relevance
“…1,2,3, 4,5,6,7,8). It was found that the response of glassy matter to high electrical fields goes far beyond the rather trivial polarization saturation effects investigated in some pioneering works on nonlinear dielectric properties (e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1,2,3, 4,5,6,7,8). It was found that the response of glassy matter to high electrical fields goes far beyond the rather trivial polarization saturation effects investigated in some pioneering works on nonlinear dielectric properties (e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…However, in this plastic crystal the detected cooperativity seems to lead to much weaker slowing down of molecular dynamics than in the canonical glass formers. 8 Unfortunately, until now cyclo-octanol seems to be the only plastic crystal were higher harmonics of the susceptibility were reported and further measurements are needed to check for the possible universality of these findings.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations